LONELINESS IN OVERSEAS CHILDREN WHO STUDY IN GRESIK CAMPUS - Prautama, Dicky Aldisar; Amelasasih, Prianggi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Loneliness is a psychological condition commonly experienced by migrant students who must adapt to new environments far from their families. This study explores the subjective experiences of loneliness among rantau (migrant) students studying at several universities in Gresik, Indonesia. The research aims to identify the factors contributing to loneliness, its emotional and behavioral impacts, and the coping strategies adopted by students. Using a qualitative descriptive approach, data were collected through semi-structured in-depth interviews with three participants from different universities: Aira (Politeknik Semen Indonesia), Citra (Universitas Internasional Semen Indonesia), and Ferismaldy (Universitas Muhammadiyah Gresik). The results indicate that loneliness arises from limited intimate relationships, difficulties in communication, and emotional distance from family. Personality traits such as introversion and low self-confidence intensify feelings of isolation. The psychological effects include sadness, decreased motivation, loss of appetite, sleep disturbances, and a sense of worthlessness. However, several participants were able to reduce loneliness through positive coping mechanisms, including engaging in part-time work, joining campus organizations, and maintaining close friendships. This study concludes that loneliness among rantau students is a multidimensional experience shaped by personal, social, and environmental interactions.